2014
DOI: 10.1007/s10337-014-2638-4
|View full text |Cite
|
Sign up to set email alerts
|

LC–MS/MS Method for the Simultaneous Determination of Free Urinary Steroids

Abstract: Cortisol homeostasis is implicated in hypertension and metabolic syndrome. Two enzymes modulate cortisol availability; 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) preferentially converts inactive cortisone to cortisol, whereas 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) converts cortisol to cortisone. In contrast, 5α and 5β reductases inactivate cortisol by conversion to its tetrahydrometabolites: tetrahydrocortisol, allo-tetrahydrocortisol and tetrahydrocortisone. A subtle local increase in cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…The limits of detection (LODs) using nanoLC/MS/MS were found to be 7.8 fg/μL, 7.2 fg/μL and 9 fg/μL for progesterone, testosterone and hydrocortisone, respectively. These LODs are an improvement compared to that reported for the analysis of urinary steroids using conventional LC where the LOD was 50 fg/μL . This improvement in sensitivity over conventional LC is of particular importance where the sample quantity is limited.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The limits of detection (LODs) using nanoLC/MS/MS were found to be 7.8 fg/μL, 7.2 fg/μL and 9 fg/μL for progesterone, testosterone and hydrocortisone, respectively. These LODs are an improvement compared to that reported for the analysis of urinary steroids using conventional LC where the LOD was 50 fg/μL . This improvement in sensitivity over conventional LC is of particular importance where the sample quantity is limited.…”
Section: Resultssupporting
confidence: 92%
“…Steroid hormone analyses using LC/MS/MS techniques have been conducted in various species and tissues . Although there has been great utility of nanoLC/MS/MS for peptide analysis due the increased sensitivity of this method, there has been limited use of nanoLC/MS/MS for steroids.…”
mentioning
confidence: 99%
“…Deuterium isotope effect caused [ 2 H 6 ]-A-THF to elute 0.5 min earlier than the unlabeled THF and A-THF (Supplementary Figure 4A). Previous studies reported a partial separation of THF and A-THF by using chromatographic condition with 0.1% acetic acid or formic acid (FA) [9,25]. However, we observed considerable ion suppression and lost 40-80% ion signals of cortisol metabolites when the concentration of FA increased from 0.01 to 0.05%, and 0.1% during optimization of chromatographic conditions.…”
Section: Resultsmentioning
confidence: 63%
“…LOD and LOQ values of cortisol metabolites were summarized in Table 1. Sensitivities were achieved for cortisol and cortisone in the urine with LOD as low as 0.05 and 0.02 pg/μl urine, respectively, 10-75-times more sensitive than the methods in previous reports [9,25]. LOD and LOQ estimates were higher for A-THF/THF, 6-hydroxycortisol, dihydrocortisol, THE and dihydrocortisone, likely because these compounds were labile under ESI and underwent in-source fragmentation to lose H 2 O molecules in the full MS scan, which caused a drop of ion signals measured at MS 2 and MS 3 scan stages.…”
Section: Methods Validationmentioning
confidence: 72%
“…Human blood, saliva, and urine are biofluids that constitute a source of non-invasive, convenient and easy to access biomarkers that can be collected many times over long periods of time. Spot urine and 24-h urine is the focus for the identification of novel peptide, steroidal, or exosomal biomarkers with a potential role in diagnosis and classification of diseases related to renal system ( 65 , 66 ).…”
Section: Exosomes and Exosomal Cargo Are Potential Novel Biomarkers Fmentioning
confidence: 99%